Analisis Feminisme pada Tokoh Perempuan “Jebris” dalam Antologi Drama Mata yang Enak Dipandang Adaptasi Kumpulan Cerpen Ahmad Tohari - Ega Dany Pratama; Cintya Nurika Irma (Fonologi: Jurnal Ilmuan Bahasa dan Sastra Inggris, 2025)
This journal examines the Marxist feminist approach in literature, focusing on the character Jebris in the drama anthology “Mata yang Enak Dipandang,” which is an adaptation of Ahmad Tohari’s short stories. The study explores three main aspects: societal, economic, and political, to identify Jebris’ role and representation from a Marxist feminist perspective. The analysis aims to provide deeper insights into how Marxist feminist theory is reflected in the character of Jebris and its impact on the overall narrative of the adapted literary work. The research method involves textual and social context analysis to provide a profound interpretation of Jebris’ thoughts and role in reflecting relevant gender and social issues. The findings of this research contribute to understanding the relationship between Marxist feminist theory and literature, while offering critical perspectives on gender representation in adapted literary works.